THE IMPLEMENTATION OF DYNAMIC ASSESMENT STRATEGIES BASED ON THE MORAL AND RELIGIOUS VALUES TOWARD THE EARLY CHILDHOOD - Maulida Maulida (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2019)
This study uses qualitative methods of observation, interviews, and documentation studies. This problem is motivated by a child who experiences delays in the development of religious and moral values. The purpose of this study is to describe how teachers implement dynamic assessment strategies based on moral values ​​in children aged 4-5 years. Then the data were analyzed using Miles & Huberman analysis. The results show that the form of research used by the teacher concerned for children with the initials BC is a form of observation checklist assessment, portfolio worksheets, anecdotes. Various ways and activities applied by teachers in providing stimulus to children with the initials BC. Children with the initials BC have experienced the development of moral religious values, and the level of development of children is at the stage of developing (MB). Keywords: Dynamic assessment, development, moral religious values